Assessment in English for Specific Purposes through Integrated Skills - Zaki, Zabihullah (Integrated Journal for Research in Arts and Humanities, 2022)
The article discusses a review of key areas of knowledge and skills in language assessment in English for specific purposes (ESP) teachers and learners, as well as language teacher educators and other language professionals. The study provides insights regarding the reasons for providing both teachers and learners with opportunities to acquire and develop assessment-related knowledge and integrated skills of writing, reading, listening and speaking. The present study also aims to demonstrate the advantages of using assessment in the ESP (English for Specific Purposes) class. By resorting to theoretical support and also practical examples from professional experience, the researcher argues that employing assessment to check the level of the English language skills for students is a beneficial factor for general language progress in the context of specific content language required by the students’ educational outline.